The future of internal medicine in the United States and Poland - Wilson, Candace M.; Taylor, Olusegun; Prystupa, Andrzej; Załuska, Wojciech (Polish Journal of Public Health, 2014)
Internal medicine physicians are critical to the health of the population. Internal medicine doctors also bring cost savings in health care because they treat many systems in the body and treat the patients in a holistic manner. However, the popularity of the specialty of internal medicine is declining. This is due to the decreased compensation that internal medicine doctors obtain when compared to their colleagues who specialize in other fields. The decline in number of physicians specializing in internal medicine causes a decrease in the health of the population. Governments and policy makers must look for ways to reverse the trend of doctors not specializing in internal medicine.